PENDAMPINGAN PEMBERDAYAAN EKOWISATA PERAIRAN DAN RESTOCKING UDANG GALAH (MACROBRACHIUM ROSENBERGII) SERTA IKAN ENDEMIK DI DAERAH ALIRAN SUNGAI (DAS) DESA GALUNGAN KABUPATEN BULELENG - I Ketut Wija Negara; I Wayan Restu; Pande Gde Sasmita Julyantoro; Endang Wulandari Suryaningtyas; Dewa Ayu Angga Pebriani; Ni Putu Putri Wijayanti; Suprabadevi Ayumayasari Saraswati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2020)
The total tourist arrivals in Buleleng Regency from 2012-2016 averaged 669,005 annually. Galungan Village is located in the District of Sawan, which has an area of 14.60 km2 with part of its territory contained State Forest covering an area of 582 Ha and traversed by several Watersheds. The method used to achieve these objectives is through mentoring in the field of education, ecotourism study simulations increasing human resources in the organization of tourism awareness groups and encouraging the formation of supervisory community groups, restocking giant prawns (Macrobrachium rosenbergii) and upstream endemic fish (waterfalls) as a tourist attraction. The potentials of Galungan Village are forests, rivers, and communities of that environment. Besides that, the climate of this village is potential for the development of a tourist village. The Galungan Village supervisor community has a very important role in managing the efforts to develop village tourism. Conservation of the environment through the maintenance and nursery of endemic fish in watersheds can be one factor to provide other attractions besides the beauty of the forest and waterfalls in Galungan Village